MUSIC THERAPY FOR PEOPLE IN A DISABILITY SITUATION: METHODOLOGY AND PROCESS - Latakienė, Jurgita; Baranauskienė, Ingrida (Education Reform: Education Content Research and Implementation Problems, 2019)
The research was constructed on the ground of the ideas of postpositivism, when the research data based on personal experience is of not lesser importance than “clinical” evidence. Our research aimed at answering the following questions: At what extent is music theory useful to people with mental disability? At what extent are the authorial methods of application of music theory designed by the investigators useful? At what extent are the participants able to express their feelings and evaluate the process of music therapy? The initial research results suggest that the authorial methods based on the ecological systems theory are effective and useful to the practice of social work in the Occupational Day Centre while providing services to individuals with mental disabilities. The obtained research data allows stating that the way chosen by the investigators to assess effectiveness of music therapy (filling in small books and conversations while filling them in) enables participants reveal their condition, feelings as well as evaluate the process of music therapy.